Market orientation at universities: construct and exploratory validation - Rivera-Camino, Jaime (2010)
Faced with a panorama of growing competitiveness in which universities are forced to get resources on their own, the concept of market orientation can be seen as a solution backed by ample literature. However, the existing literature is based principally on the profit-making sector with the publications in the educational field being still scarce. The purpose of our exploratory research is to develop and validate a market orientation measure in a sampling of Spanish universities. The scale integrates and expands the theoretical proposals from previous research; it shows acceptable levels of reliability and validity while allowing the setting-up of future lines of research in the area.